Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/scan/nsz006
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of cognitive control networks by monetary reward and punishment

Abstract: Incentives are primary determinants of if and how well an organism will perform a given behavior. Here, we examined how incentive valence and magnitude influence task switching, a critical cognitive control process, and test the predictions that the anterior cingulate cortex (ACC) and the ventral striatum (vStr) function as key nodes linking motivation and control systems in the brain. Our results indicate that reward and punishment incentives have both common and distinct effects on cognitive control at the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 78 publications
6
24
0
Order By: Relevance
“…In Experiment 3 on the other hand, losses were associated with better working memory performance only at the highest effort level (4-Back). These mixed findings concur with previous studies, some of which found no difference in performance between gain and loss conditions in a 3-Back task (Belayachi et al, 2015 ), while other studies found that loss incentives could even impair performance on other tasks (switch task, Stroop task, flanker task; Paschke et al, 2015 ; Carsten et al, 2019 ; Cubillo et al, 2019 ). Possibly, the effects of loss incentives may depend on the nature of the task (e.g., differentially affecting proactive vs. reactive control processes; Chiew and Braver, 2013 ; Botvinick and Braver, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…In Experiment 3 on the other hand, losses were associated with better working memory performance only at the highest effort level (4-Back). These mixed findings concur with previous studies, some of which found no difference in performance between gain and loss conditions in a 3-Back task (Belayachi et al, 2015 ), while other studies found that loss incentives could even impair performance on other tasks (switch task, Stroop task, flanker task; Paschke et al, 2015 ; Carsten et al, 2019 ; Cubillo et al, 2019 ). Possibly, the effects of loss incentives may depend on the nature of the task (e.g., differentially affecting proactive vs. reactive control processes; Chiew and Braver, 2013 ; Botvinick and Braver, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…It is the case that we cannot rule out that “gain” incentives would have had similar results in the present study; the complementary criticism applies to the majority of studies that have focused solely on gain incentives. Behavioral ( O’Brien and Hess, 2019 ) and neural (e.g., Paschke et al, 2015 ; Cubillo et al, 2019 ) evidence suggests that gain and loss operate through partially independent processes. However, this issue needs further examination, and in general, studies in this field would benefit from including both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Scenario 2 assumed a weak dissociation between the treatment of PG and PL, as to accommodate the manifolds studies reporting partially distinct neural substrates and behavioral effects of reward and punishments (e.g. Cubillo, Makwana, & Hare, 2019).…”
Section: Figurementioning
confidence: 99%